Transcendentality and Historicity: Derrida Reader of Husserl - Onate, Alberto Marcos (Veritas (Porto Alegre), 2013)
The present article seeks to reconstruct the relationship between the French and German thinkers, adopting the theme of history as a thread. The key question concerns the possibility of developing a transcendental history. Such a history, if feasible, would provide a historicity, as it would have to describe the genesis of meaning(s) in the necessary and unavoidable exchange between the transcencendental and empirical dimensions. The question is how to reduce the various egoic, temporal, and intersubjective phenomena, without losing the empirical domain in which they take root? This is the major challenge posed by Derrida’s texts on the work of Husserl.